Implementation of E-Procurement in Micro, Small and Medium Enterprises (MSMEs) in Yogyakarta - Reni Listyawati; Uum Helmina Chaerunisak; Sri Lestari Yuli Prastyatini (Faculty of Economics Universitas Sarjanawiyata Tamansiswa, 2023)
PurposeCommunity Service (Abdimas) activities carried out at the MSME